Liomera rugipes (Heller, 1861) (Brachyura: Xanthidae: Liomerinae): a new Indo-West Pacific crab in the Mediterranean Sea, Egypt - NOUR, OLA MOHAMED; ZAVA, BRUNO; CORSINI-FOKA, MARIA (Mediterranean Marine Science, 2023)
A single specimen of the xanthid Liomera rugipes was collected in May 2023 in the waters off Alexandria, Egypt, with a trammel net at 15 m of depth. The occurrence of this crab is reported for the first time in the Mediterranean Sea and adds a new Indo- West Pacific crab to the non-indigenous biota of the basin, probably introduced via the Suez Canal. This new finding increases the number of Egyptian non-indigenous brachyurans to 21 species.